2017
DOI: 10.1186/s13071-017-2509-6
|View full text |Cite
|
Sign up to set email alerts
|

Germacranolide-type sesquiterpene lactones from Smallanthus sonchifolius with promising activity against Leishmania mexicana and Trypanosoma cruzi

Abstract: BackgroundLeishmaniasis and Chagas disease are life-threatening illnesses caused by the protozoan parasites Leishmania spp. and Trypanosoma cruzi, respectively. They are known as “neglected diseases” due to the lack of effective drug treatments and the scarcity of research work devoted to them. Therefore, the development of novel and effective drugs is an important and urgent need. Natural products are an important source of bioactive molecules for the development of new drugs. In this study, we evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Sesquiterpene lactones (SL) are 15‐carbon terpenoids organized in different cyclic hydrocarbon skeletons containing a fused lactone ring . Considered as chemotaxonomic markers for the Asteraceae family, SL are metabolites of great interest because of their antiproliferative and antitumor, anti‐inflammatory, and antiprotozoal properties. Over 30 different skeletons have been described in the literature including hirsutinolide and glaucolide‐subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Sesquiterpene lactones (SL) are 15‐carbon terpenoids organized in different cyclic hydrocarbon skeletons containing a fused lactone ring . Considered as chemotaxonomic markers for the Asteraceae family, SL are metabolites of great interest because of their antiproliferative and antitumor, anti‐inflammatory, and antiprotozoal properties. Over 30 different skeletons have been described in the literature including hirsutinolide and glaucolide‐subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…The action of these sesquiterpene lactones was better than the positive control, amphotericin B (IC50 = 2 μM). As seen with the anti- T. cruzi activity, the highest activity toward intracellular form of L. mexicana was observed for uvedalin (IC50 = 1.89 μM), followed for enhydrin (IC50 = 3.66 μM; Ulloa et al, 2017).…”
Section: Sesquiterpene Lactones From Smallanthus Sonchifolius Are Actmentioning
confidence: 82%
“…The animals treated with uvedalin or enhydrin exhibited lower levels of parasitaemia, and these effects were similar to those obtained with benznidazole (positive control). Mice treated with these sesquiterpene lactones also showed higher survival ratios and reduced weight loss when compared to untreated animals (Ulloa et al, 2017).…”
Section: Sesquiterpene Lactones From Smallanthus Sonchifolius Are Actmentioning
confidence: 99%
“…H. Rob. and evaluated against T. cruzi epimastigotes, using benzonidazole as positive control [ 66 ]. Compounds 42 and 43 showed identical activities with IC 50 values of 0.78 and 0.79 μM, respectively.…”
Section: Terpenic Compounds With Antitrypanosomal Activitymentioning
confidence: 99%
“…A significant decrease in circulating parasites (50–71%) was observed, with no signs of toxicity in the dose administrated (1 mg/kg/day). Complementary studies showed marked ultrastructural alteration in trypanosome parasites when treated with these compounds [ 66 ].…”
Section: Terpenic Compounds With Antitrypanosomal Activitymentioning
confidence: 99%